Mathematical models for wastewater treatment plants: first applications in Friuli - CIMAROSTI, ILARIA; ROSELLIDELLAROVERE, CRISTANO; GOI, DANIELE (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
The municipal or industrial wastewater biological treatment before discharge in rivers or other hydrological bodies, is the most common system to remove or minimize the pollution of wastewater. The activated sludge system is the most famous biological system for wastewater treatment. The activated sludge treatment removes the soluble organic and inorganic materials and coagulates unsettable and colloidal solids by the microorganisms that compose the sludge. The study of biochemical processes involved in wastewater biologic treatment has determined a new approach to planning: the modellistic approach. This article presents an introduction to the underlying mathematical theory and some real-case experiences with this model. The microorganisms that compose the activated sludge are called biomass, while pollutants are called substrate. The biomass is allowed to grow using pollutants as sources of carbon and/or energy, removing them pollutants from the wastewater by converting them in new biomass, H2O e CO2. There are different kinds of microorganisms which are classified into heterotrophs and autotrophs as they utilize oxygen or carbon substance as electron acceptor. The main pollutant substances to be removed by biological treatments are carbon compounds, nitrogen and phosphate. This issues has been intriguing many universities and research centers abroad for a long time now. In particular, in 1987 the Task Group of I.A.W.Q. (International Association on Water Quality) formulated the Activated Sludge Model N. 1 that has been applied several times and whose validity and reliability has been demonstrated. The A.S.M. N. 1 considers removal of carbon and nitrogen. Increasingly complex models have been formulated in recent years which also consider removing phosphate (A.S.M. N. 2 and 3). The Chemical Department of the University of Udine has been studying the modellistic approach to planning/managing of wastewater treatment plants for some years now by the A.S.M. N. 1 which is described below.